Knowledge Management and Intellectual Capital: Key Drivers of University Performance in Saudi Arabia (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to examine the interrelationships between knowledge management infrastructure, knowledge management processes, intellectual capital, and organizational performance. To achieve this objective, a quantitative approach was employed, utilizing a structured questionnaire to assess our research model with a convenience sample of 185 faculty and staff members from Saudi universities. The findings indicate that knowledge management infrastructure has a significant positive effect on knowledge management processes. Moreover, these processes positively impact both intellectual capital and organizational performance, while also strengthening the relationship between knowledge management infrastructure and intellectual capital. However, it is noteworthy that knowledge management infrastructure did not directly correlate with organizational performance. These results underscore the critical role of knowledge management processes as mediators and highlight the limitations of relying solely on infrastructure to directly enhance organizational performance.